Subjective and physiological responses to façade and sunlight pattern geometry in virtual reality. (March 2019) - Chamilothori, K.; Chinazzo, G.; Rodrigues, J.; Dan-Glauser, E.S.; Wienold, J.; Andersen, M.
Abstract: This study investigates the joint impact of façade geometry and associated sunlight patterns on occupant subjective perception and physiological responses through a novel experimental method coupling physically-based simulations shown in virtual reality with a wearable biometric device. A total of 72 subjects participated in a study combining three façade configurations of an equal aperture ratio with different scenarios of space use (a social or working context). The façade variations –a non-uniform distribution of openings ("Irregular"), a uniform distribution of openings ("Regular") and venetian blinds ("Blinds")– were applied to an interior scene with clear sky and direct sun penetration. Subjective evaluations (how pleasant, interesting, and exciting the space was perceived) and physiological responses (heart rate and skin conductance) were collected during exposure to façade variations, while a neutral scene was used to record baseline physiological responses. Results revealed that façade and sunlight pattern geometry significantly influenced subjective responses for both context scenarios, while subsequent analyses showed differences mostly between the Irregular and Regular conditions, with the former being evaluated more positively. Façade and sunlight pattern geometry affected heart rate responses, but not skin conductance responses. In particular, participants showed a larger decrease in heart rate while exposed to the Irregular condition compared to the Blinds. Context scenarios influenced evaluations of interest and excitement. Findings are particularly relevant for applications in architecture and lighting, demonstrating that façade elements and their interaction with light can influence occupant subjective and physiological responses, and showcasing the potential of the presented method for investigating human perception. ghts: Façade and sunlight pattern geometry affect participants' subjective responses. Façade and sunlight pattern geometry affect participants' mean heart rate change. Non-uniformly distributed openings led to lower mean heart rate than venetian blinds. Non-uniformly distributed openings were preferred to uniformly distributed openings. Space use scenarios influence how interesting and exciting a space is perceived.